The Governmental Habit Redux : Economic Controls from Colonial Times to the Present. - Hughes, Jonathan R. T. (Princeton legacy library., 2014)
To the distinguished economic historian Jonathan Hughes, the ambiguous outcomes of attempted deregulation signal America's urgent need to probe the origins of our vast and chaotic maze of government economic controls. Why do government restrictions on the economy continue to proliferate, in spite of avowed efforts to allow the market a freer rein? How did this complicated network of nonmarket economic controls come about and whose purposes does it serve? How can we render such controls less destructive of productivity and wealth-creating activity? While exploring these questions, Jonathan H.